The use of flexible working contracts in West Germany: evidence from an establishment panel - Bernhard Boockmann; Tobias Hagen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper investigates under which conditions firms use fixed-term contracts, subcontracted and freelance work. Using a probit model which accounts for unobserved heterogeneity, we find that positive changes in expected or actual turnover are associated with a higher probability of employing atypical work, which suggests that these forms of employment are used as means of adjustment. Other important factors are employees? skill levels, investment in information technology, and the existence of collective wage agreements and works councils. Furthermore, a natural experiment is used to evaluate the impact of dismissal protection for permanent workers on the use of flexible working contracts. There is clear evidence that reducing dismissal protection decreases the demand for fixed-term employment.
Keywords: J42; J23; C23; 330; Flexible working contracts; fixed-term employment; labour demand; adjustment costs; Befristeter Arbeitsvertrag; Arbeitsnachfrage; Arbeitsmobilität; Qualifikation; Ungeschützte Beschäftigung; Kündigungsschutz; Betriebsrat; Schätzung; Deutschland